The study of ancient history, religion, culture of South, South-East and East Asia in Uzbekistan - Prof. N.G Nizomiddinov (Genius Journals, 2023)
The study of above mentioned subject on the basis of national mentality is an initial step in the years of Independence of Uzbekistan. Because, such a positive approach to the sources of spiritual values, if on the one hand, helps to feel initial oneness of mankind noted in divine messages; on the other hand, it creates mutual understanding among the nations with different faiths, which is important today in struggling against the international extremism and terrorism. By the way, «All religions», - as a well-known sufi Mansoor Khallaj said, - «are the different twigs of one and the same Tree.» In accordance with this view-point, in our investigation we tried to continue the tradition of Abu Reikhan Beruni, who over a thousand years ago created the scientific method of comparative study of the world national values – history, religions, culture and traditions
Keywords: sansara; sutra; sunyasi; tirthankar